Genomic features, antimicrobial susceptibility, and epidemiological insights into Burkholderia cenocepacia clonal complex 31 isolates from bloodstream infections in India - Saroha, Tanu; Patil, Prashant P.; Rana, Rekha; Kumar, Rajesh; Kumar, Sanjeet; Singhal, Lipika; Gautam, Vikas; Patil, Prabhu B. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Burkholderia cepacia complex (Bcc) clonal complex (CC) 31, the predominant lineage causing devastating outbreaks globally, has been a growing concern of infections in non-cystic fibrosis (NCF) patients in India. B. cenocepacia is very challenging to treat owing to its virulence determinants and antibiotic resistance. Improving the management of these infections requires a better knowledge of their resistance patterns and mechanisms. Methods Whole-genome sequences of 35 CC31 isolates obtained from patient samples, were analyzed against available 210 CC31 genomes in the NCBI database to glean details of resistance, virulence, mobile elements, and phylogenetic markers to study genomic diversity and evolution of CC31 lineage in India. Results Genomic analysis revealed that 35 isolates belonging to CC31 were categorized into 11 sequence types (ST), of which five STs were reported exclusively from India. Phylogenetic analysis classified 245 CC31 isolates into eight distinct clades (I-VIII) and unveiled that NCF isolates are evolving independently from the global cystic fibrosis (CF) isolates forming a distinct clade. The detection rate of seven classes of antibiotic-related genes in 35 isolates was 35 (100%) for tetracyclines, aminoglycosides, and fluoroquinolones; 26 (74.2%) for sulphonamides and phenicols; 7 (20%) for beta-lactamases; and 1 (2.8%) for trimethoprim resistance genes. Additionally, 3 (8.5%) NCF isolates were resistant to disinfecting agents and antiseptics. Antimicrobial susceptibility testing revealed that majority of NCF isolates were resistant to chloramphenicol (77%) and levofloxacin (34%). NCF isolates have a comparable number of virulence genes to CF isolates. A well-studied pathogenicity island of B. cenocepacia, GI11 is present in ST628 and ST709 isolates from the Indian Bcc population. In contrast, genomic island GI15 (highly similar to the island found in B. pseudomallei strain EY1) is exclusively reported in ST839 and ST824 isolates from two different locations in India. Horizontal acquisition of lytic phage ST79 of pathogenic B. pseudomallei is demonstrated in ST628 isolates Bcc1463, Bcc29163, and BccR4654 amongst CC31 lineage. Discussion The study reveals a high diversity of CC31 lineages among B. cenocepacia isolates from India. The extensive information from this study will facilitate the development of rapid diagnostic and novel therapeutic approaches to manage B. cenocepacia infections.